Interactions among nutrition, metabolism and the immune system in the context of starvation and nutrition-stimulated obesity - Borros Arneth (Nutrition & Diabetes)
Abstract The endogenous intestinal microflora and environmental factors, such as diet, play central roles in immune homeostasis and reactivity. The microflora and diet both influence body weight and insulin resistance, notably through their effects on adipose cells. The aim of this study was to provide an update on how nutrient-derived factors (mostly focusing on fatty acids and glucose) impact the innate and acquired immune systems, including the immune system in the gut and its associated bacterial flora. The main source of fuel for energy-demanding immune cells is glucose. Insulin-responsive adipose tissue and Toll-like receptors (TLRs), which are part of the innate immune system and expressed in immune cells, intestinal cells, and adipocytes, are essential actors in the complex balance that ensures systemic immune and metabolic health. Leptin decreases during weight loss and increases brain activity in regions involved in the cognitive, emotional, and sensory control of food intake; restoring leptin levels maintains weight loss and reverses the alterations in brain activity. Obesity-triggering nutrients affect adipocytes, whereas proinflammatory leptin prompts the generation of cytokines and T cells. Collectively, data on nutrients demonstrate that starvation culminates in fat depletion, which then impacts the immune system. In people with obesity, inflammation originates largely from adipose tissue.